PECULIARITIES OF RESTRICTION OF HUMAN AND CIVIL RIGHTS UNDER MARTIAL LAW - Netska, Lyubov; Chaika, Kateryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to establish the limits of possible interference with human and citizen rights in the conditions of martial law and the compliance of the introduced restrictions on human rights with the norms of the Constitution of Ukraine. Research methods: formal-legal, analysis and synthesis, comparative-legal, logical. Results: it is proved that in a democratic society legitimate restrictions of human rights can be applied, the specifics of the restriction of various human and citizen rights during the introduction of martial law are determined, the conditions under which these restrictions can be justified as temporary measures to ensure the security and protection of the state in a crisis situation are outlined, it is concluded that restrictions on human rights should be proportionate and apply only to those rights whose restriction is necessary. Discussion: it is emphasized that one of the main problems is finding a balance between the need to ensure the security of the state in the conditions of a military conflict and the preservation of the basic rights and freedoms of citizens. Often restrictions on rights are introduced as temporary measures, but it is important to define the limit of these restrictions. It is emphasized that the list of rights, the limitation of which is permissible, and the actual limits of the reduction of the scope of rights permitted by law need to be clarified. Some human and citizen rights and freedoms provided for by the Basic Law of Ukraine are not absolute. It is important to observe the permissible legal limits of interference with human rights in order to prevent abuse of their limitations.